Strengthening Internal Controls Over Drug Inventory: Insights from a Case Study at PT ABC Pharmacy - Prathama, Yudha Rahadian; Harahap, Siti Nurwahyuningsih (E-Jurnal Akuntansi; Vol 35 No 3 (2025), 2025)
This study evaluates the effectiveness of internal control over drug inventory at ABC Pharmacy, which is essential for operational continuity and healthcare quality. Weak controls can lead to overstocking, damage, and expired drugs, harming finances and reputation. The study using a qualitative case study method and referring to the COSO (2013) framework focusing on risk assessment and control activities, data were obtained through semi-structured interviews and document analysis. The findings show that although internal controls exist, several weaknesses remain. The company lacks a risk register and systematic risk assessment. Storage is not supported by SOPs applying the First Expired First Out (FEFO) method, and documentation for drug distribution is inadequate. These findings suggest the need for improved policies, formal procedures, and the development of internal control awareness across all levels. Keywords: Internal Control, Drug Inventory, COSO, Pharmacy, FEFO